Design and development of a solar refrigeration system - RAKHI J. F; Er. George Mathew (Guide) (Tava 2015 Department Food and Agricultural Process Engineering)
Solar energy, a vast and inexhaustible source of energy, is one of the most promising sources of non conventional energy currently available.
Design and development of a solar refrigeration system